2021
DOI: 10.3389/fvets.2021.692521
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vaccination Reduces the Effects of Lawsonia intracellularis Challenge on the Swine Small and Large Intestine Microbiome

Abstract: Porcine proliferative enteropathy remains one of the most prevalent diseases in swine herds worldwide. This disease is caused by Lawsonia intracellularis, an intracellular bacterial pathogen that primarily colonizes the ileum. In this study, we evaluated changes to the microbiome of the ileal mucosa, ileal digesta, cecal digesta, and feces subsequent to challenge with L. intracellularis and to an oral live vaccine against L. intracellularis. Given that gut homogenates have been used since 1931 to study this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 42 publications
4
12
1
Order By: Relevance
“…Muwonge et al (26) found the top three families Prevotellaceae, Ruminococcaceae, and Lactobacillaceae as the core microbiota in their study to be associated with changes in the threshold for shedding L. intracellularis, but not to have a major effect on the clinical outcome of the disease. Some Prevotella species were found to be decreased due to oral L. intracellularis vaccination in the present study as well as in investigations by Leite et al (12,24), who found one Prevotella species to be increased in the former study and two Prevotella species to be increased and two to be decreased in the latter study due to oral L. intracellularis vaccination. Prevotella is a genus with high genetic diversity within and between species, and certain strains may exhibit pathobiontic properties by promoting chronic inflammation in humans (56,57).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Muwonge et al (26) found the top three families Prevotellaceae, Ruminococcaceae, and Lactobacillaceae as the core microbiota in their study to be associated with changes in the threshold for shedding L. intracellularis, but not to have a major effect on the clinical outcome of the disease. Some Prevotella species were found to be decreased due to oral L. intracellularis vaccination in the present study as well as in investigations by Leite et al (12,24), who found one Prevotella species to be increased in the former study and two Prevotella species to be increased and two to be decreased in the latter study due to oral L. intracellularis vaccination. Prevotella is a genus with high genetic diversity within and between species, and certain strains may exhibit pathobiontic properties by promoting chronic inflammation in humans (56,57).…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, the existing differences in terms of OTUs differing between the two groups (Collinsella aerofaciens, Prevotella copri, and Clostridiales) resemble previous investigations with experimental L. intracellularis challenge, that have also shown that oral vaccination against L. intracellularis shapes the gut microbiota in weaned piglets. Leite et al (12,24) who investigated the impact of an oral live vaccine against L. intracellularis (Enterisol R Ileitis) in pigs experimentally challenged with L. intracellularis were in line with results of the present study. Vaccination against L. intracellularis in dually challenged pigs (L. intracellularis and S. enterica serovar Typhimurium) also induced a significant decrease in abundance of an OTU that closely matched Collinsella aerofaciens and a significant increase in the abundance of Clostridium species (24).…”
Section: Impact Of Oral Vaccination On Microbiotasupporting
confidence: 91%
See 3 more Smart Citations